Partial replacement of fish meal by soybean meal supplemented with inulin and oligofructose in the diet of pikeperch (Sander lucioperca): Effect on growth and health status - Dadras, Hadiseh; Chupani, Latifeh; Imentai, Aiman; Malinovskyi, Oleksandr; Esteban, Maria Angeles; Penka, Tomas; Kolářová, Jitka; Rahimnejad, Samad; Policar, Tomáš (Frontiers in Marine Science, 2022)
A diet containing FM was considered as the basal diet, and then three other diets were prepared by: 1) replacing 50% of FM with SM (SM50), 2) replacing 50% of FM with SM and supplementation of 2% inulin (SMI50), and 3) replacing 50% of FM with SM and supplementation of 2% oligofructose (SMO50). The group fed SMO50 showed the highest weight gain (WG; 85.85 ± 4.46 %) among the groups fed SM, with no significant difference from the FM group (79.74 ± 2.04 %; p > 0.05). A lower SGR (0.69 ± 0.09 %) was observed in the SM50 group without the supplementation of 2% inulin or oligofructose compared to the group fed FM (p < 0.05). A significant difference in FCR was found between the SM50-fed group without supplementation of inulin or oligofructose (1.50 ± 0.13) and the group fed FM (0.97 ± 0.04). Survival rate and whole-body composition showed no significant difference among all groups (p > 0.05). A significant decrease in serum total cholesterol concentration was observed in the SMO50 group (2.10 ± 0.29 mmole L-1) compared to the FM-fed group (3.33 ± 0.33 mmole L-1). The concentrations of other serum biochemical parameters (total protein, glucose, lactate dehydrogenase, alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were not significantly affected by the dietary treatments (p > 0.05). Among all innate immunity and antioxidant parameters, only the serum malondialdehyde (MDA) concentration of SM50-fed fish (4.25 ± 0.7 nmole mL−1) was significantly lower than in the FM-fed group (with the highest MDA concentration; 25.17 ± 3.13 nmole mL−1). No significant differences were found in the relative expression of IGF-I, IGF-II, GHR genes among the studied groups (p> 0.05). The results of the present study show that 50% replacement of FM with SM supplemented with a small amount of oligofructose (2% of dry matter) does not compromise the growth performance or the immune system of pikeperch. This substitution is feasible and provides a reference for cost-optimised design of feed formulation for pikeperch.